SmartCityOS: Making Tomorrow Smarter - H. Xu; H. Xu; H. Xu; H. Xu; H. Xu; B. He; B. He; B. He; B. He; C. Zhang; C. Zhang; C. Zhang; et al. (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
With the rapid advancement and widespread adoption of information and communication technology, the information space has emerged as the third space, complementing the physical and social spaces to form the ternary space of human society. The coupling of the ternary space promotes urban development, leading to a new paradigm: the smart city, representing the intelligent transformation of cities within the ternary space. Smart cities are giant, open, and complex systems that integrate diverse information systems rather than simply aggregating them. They create a systematic ecosystem of interconnected systems, all relying on shared infrastructure and data resources with substantial operational overlaps. This interconnectivity necessitates the development of a Smart City Operating System (SmartCityOS). Geographic information systems (GIS) are utilized to establish connections between the ternary space, mapping the city’s physical and social spaces into the information space. The information space then feeds back into the physical and social spaces, optimizing urban systems and delivering open, diverse, shared, and environmentally sustainable intelligent applications. The concept and scope of the SmartCityOS are explained through its logical layers and system architecture. Key technologies, including ubiquitous city perception, digital modeling, spatio-temporal big data fusion and analysis, 3D city visualization, and simulation and digital twin interaction, are emphasized as critical areas of focus. Essentially, the SmartCityOS abstracts the complexities of a heterogeneous environment, while facilitating open and diverse applications. It transitions from vertical to horizontal integration, embracing complexity while fostering innovation through openness.